Resveratrol and Its Analogs: Potent Agents to Reverse Epithelial-to-Mesenchymal Transition in Tumors - Guo, Kaibo; Feng, Yuqian; Zheng, Xueer; Sun, Leitao; Wasan, Harpreet S.; Ruan, Shanming; Shen, Minhe (Frontiers in Oncology, 2021)
Abstract: Epithelial-to-mesenchymal transition (EMT), a complicated programme through which polarized epithelial cells acquire motile mesothelial traits, is regulated by tumor microenvironment. EMT is involved in tumor progression, invasion and metastasis via reconstructing the cytoskeleton and degrading the tumor basement membrane. Accumulating evidence shows that resveratrol, as a non-flavonoid polyphenol, can reverse EMT and inhibit invasion and migration of human tumors via diverse mechanisms and signaling pathways. In the present review, we will summarize the detailed mechanisms and pathways by which resveratrol and its analogs (e.g. Triacetyl resveratrol, 3,5,4'-Trimethoxystilbene) might regulate the EMT process in cancer cells to better understand their potential as novel anti-tumor agents. Resveratrol can also reverse chemoresistance via EMT inhibition and improvement of the antiproliferative effects of conventional treatments. Therefore, resveratrol and its analogs have the potential to become novel adjunctive agents to inhibit cancer metastasis, which might be partly related to their blocking of the EMT process.